The Implementation of Restorative Justice for Children Who Commit Crimes from the Perspective of National Law and the Qanun Jināyat - Kurniawan, Itok Dwi (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This study aims to examine the application of restorative justice for children as criminal offenders under the 2012 Juvenile Criminal Justice System Law (UU SPPA) and the 2014 Qanun Jināyat. The research is an empirical legal study that utilizes a statutory approach and the theory of restorative justice. The findings show that Article 5, paragraph (1) of the 2012 UU SPPA stipulates that children who commit criminal acts (jarīmah) must prioritize a restorative justice approach. Moreover, Article 7, paragraph (1) mentions that at the stages of investigation, prosecution, and trial of child offenders in the district court, diversion efforts must be made. The 2014 Qanun Jināyat does not specifically regulate the handling of cases involving children as offenders but refers to laws concerning juvenile justice. It outlines that the handling of children involved in jarīmah ikhtilaṭ must follow the procedures set out in the aforementioned laws. However, if a child commits an ikhtilaṭ crime and is investigated by the police, the process must be handled through restorative justice and diversion. The forms of restorative justice resolution include: reconciliation with or without compensation, returning the child to their parents/guardians, social rehabilitation, and religious rehabilitation. This study argues that restorative justice treats children offenders with dignity, focusing on fairness and the best interests of the child. It also demonstrates that the UU SPPA and Qanun Jināyat complement each other in the context of juvenile justice.